Change in electrophoretic profile of procine spermatozoal protein during epididymal transit - MOHAN, N H; SARMAH, B C; TAMULI, M K; DAS, ANUBRATA; BUJARBARUAH, K M (The Indian Journal of Animal Sciences, 2011)
Mammalian spermatozoa acquire their motility and ability to fertilize during their transit through epididynlis and are characterized with functional changes in sperm membrane proteins. The present study was undertaken to electrophoretically characterize proteins in epididymal and testicular sperms and cauda epididymal fluid to understand spermatozoal maturation process in porcine testes. The number of protein bands in testicular, epididymal spermatozoa and epididymal fluid were 22, 17 and 17 respectively. The proteins having molecular weight (MW) of 105, 97, 89, 79, 73,64,32,29,24,22,20 and 18 kilodaltons, which were present in the testicular spennatozoa could not be identified in the epididymal sperms. On the other hand, the epididymal spermatozoa expressed proteins having MW of 102,93, 82, 66, 62, 55, 28 and 21 k.ilodaltons, which were absent in testicular spermatozoa. The epididymal fluid shared proteins havingMWof 55, 52, 42 and 39 kilodaltons with testicular and epididymal spermatozoa. The elucidation of physiological events related to protein modification, appearance and masking require further studies.Â